Review of Contemporary American Fiction in the European Classroom: Teaching and Texts - Kajtár-Pinjung, Olga (AMERICANA E-journal of American Studies in Hungary, 2022)
Contemporary American Fiction in the European Classroom: Teaching and Texts Edited by Laurence W. Mazzeno and Sue Norton Cham, Switzerland: Palgrave Macmillan, 2022 349 pages ISBN 978-3-030-94165-9; ISBN 978-3-030-94166-6 (eBook)